Partial discharge monitoring in power transformers using low-cost piezoelectric sensors - Castro, Bruno [UNESP]; Clerice, Guilherme [UNESP]; Ramos, Caio [UNESP]; Andreoli, André [UNESP]; Baptista, Fabricio [UNESP]; Campos, Fernando [UNESP]; Ulson, José [UNESP] (MDPI, 2016)
Power transformers are crucial in an electric power system. Failures in transformers can affect the quality and cause interruptions in the power supply. Partial discharges are a phenomenon that can cause failures in the transformers if not properly monitored. Typically, the monitoring requires high-cost corrective maintenance or even interruptions of the power system. Therefore, the development of online non-invasive monitoring systems to detect partial discharges in power transformers has great relevance since it can reduce significant maintenance costs. Although commercial acoustic emission sensors have been used to monitor partial discharges in power transformers, they still represent a significant cost. In order to overcome this drawback, this paper presents a study of the feasibility of low-cost piezoelectric sensors to identify partial discharges in mineral insulating oil of power transformers. The analysis of the feasibility of the proposed low-cost sensor is performed by its comparison with a commercial acoustic emission sensor commonly used to detect partial discharges. The comparison between the responses in the time and frequency domain of both sensors was carried out and the experimental results indicate that the proposed piezoelectric sensors have great potential in the detection of acoustic waves generated by partial discharges in insulation oil, contributing for the popularization of this noninvasive technique.
Keywords: Acoustic emission; Dielectric; Low-cost; Partial discharge; Piezoelectric sensors; Transformer